Moje dobrodružná cesta sociologií 100 let sociologie v Brně z mého pohledu - Mareš, Petr (Masaryk University Press, 2022)
Title in English: My adventurous journey through sociology: 100 years of sociology in Brno from my point of view The book maps the century-long existence of sociology at Brno's university. At the same time the author, professor emeritus of the MU Faculty of Social Studies, reflects on his personal "adventurous journey through sociology" and presents the reader with some intellectual and ethical questions that he encountered along the way. The text is also a generational statement illustrating the inseparable connection between the field of sociology and society. The publication will interest students and graduates in sociology, as well as all those interested in the position of the social sciences in contemporary societies.